2023
DOI: 10.3390/s23020902
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tinnitus Treatment Outcomes Based on EEG Sensors and TFI Score Using Deep Learning

Abstract: Tinnitus is a hearing disorder that is characterized by the perception of sounds in the absence of an external source. Currently, there is no pharmaceutical cure for tinnitus, however, multiple therapies and interventions have been developed that improve or control associated distress and anxiety. We propose a new Artificial Intelligence (AI) algorithm as a digital prognostic health system that models electroencephalographic (EEG) data in order to predict patients’ responses to tinnitus therapies. The EEG data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…They can detect changes in brain activity and changes in connectivity (Adjamian, 2014). They have been used to evaluate the outcome of tinnitus treatment, and their association with ITFs has also been studied (Doborjeh et al., 2023; Guntensperger et al., 2019; Henderson‐Sabes et al., 2019; Zimmerman et al., 2019). Therefore, brain imaging technology may be a good choice to detect the effect of tinnitus treatment medications targeting potassium ion channels on tinnitus patients.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…They can detect changes in brain activity and changes in connectivity (Adjamian, 2014). They have been used to evaluate the outcome of tinnitus treatment, and their association with ITFs has also been studied (Doborjeh et al., 2023; Guntensperger et al., 2019; Henderson‐Sabes et al., 2019; Zimmerman et al., 2019). Therefore, brain imaging technology may be a good choice to detect the effect of tinnitus treatment medications targeting potassium ion channels on tinnitus patients.…”
Section: Potential Limitationsmentioning
confidence: 99%
“…Future implementation of neurophysiological evidence is currently being supported by innovation across three streams: commercially available low-cost mobile neuroimaging, artificial intelligence, and investment in secure data-sharing infrastructure. For example, sound-based tinnitus treatment efficacy prediction (Sanders et al, 2021;Doborjeh et al, 2023) and mindfulness efficacy were able to be predicted with 0.87 accuracy (F-score, 89%) using EEG data fed into a brain-inspired spiking neural network model (Doborjeh et al, 2019).…”
Section: Clinician and Practitioner Empowerment Will Enhance Implemen...mentioning
confidence: 99%
“…Furthermore, this approach could foster (objective) diagnostic options, tinnitus subtyping, and identification of individual treatment options like sound therapies [38]. Related to that, it was recently shown that certain EEG features such as frequency band power and functional connectivity could predict treatment response to a sound-based intervention with 98-100% accuracy [39].…”
Section: Introductionmentioning
confidence: 99%